Effect of Using Polyethylene Plastic Bags against Increased and Stable Body Temperature in Low Birth Weight Babies (LBW) in the Nicu Room of SLG Kediri Hospital - Eva Agustina Yalestyarini; Sutik; Dian Taviyanda; Elmie Muftiana; Merry Pantrista Ningrum (Universitas STRADA Indonesia, 2024)
Background: Low Birth Weight Babies often experience unstable body temperature which tends to be low/hypothermia. The method to prevent hypothermia is to use polyethylene plastic bags. Purpose: The aim of this study was to analyze the effect of using polyethylene plastic bags in the increase and stability of body temperature in LBW in the NICU room at SLG Kediri Hospital. Method: The design of this study was Quasy Experimental, using Pre Test and Post Test approaches. Sampling by Accidental Sampling. This study was conducted on 30 BBLR babies with a weight of < 2500 grams. Data collection through observation sheets with the time of conducting research in November-December 2023 in the NICU room of SLG Kediri Hospital. Data analysis used to test the influence of two variables in this study is the Wilcoxon. Results: It is known that the pre-test body temperature before the intervention using polyethylene plastic bags was < 36.5 ℃ for 28 out of 30 respondents (93%). And those who experienced an increase and stability in body temperature were 26 respondents (87%), and 4 respondents did not experience an increase and stability in body temperature. The statistical test in this study used the Wilcoxon test, the results of this statistical test obtained the Asymp value. Sig = 0.000. Conclusion: It can be concluded that the hypothesis is accepted. This means that there is a difference between the results of body temperature measurements for the pre-test and post-test. So it can be concluded that there is an influence of the use of polyethylene plastic bags on the increase and stability of body temperature in low birth weight (LBW) babies in the NICU room at SLG Kediri Hospital. The use of polyethylene plastic bags appropriately can reduce evaporation and heat loss. Plastic as a thermoplastic polymer group can prevent heat loss caused by evaporation and radiation, so as to increase the baby's temperature. In this study the baby was still placed in the incubator.